2016
DOI: 10.1007/s00264-015-3105-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of somatization and depressive symptoms on the course of pain within the first year after uncomplicated total knee replacement: a prospective study

Abstract: Psychopathologic factors, particularly somatization dysfunction, have an impact on TKR outcomes. Preoperative screening and concurrent treatment of the diagnosed psychological disorder may improve patient-perceived outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 26 publications
1
23
0
3
Order By: Relevance
“…Ali et al [8] reported that anxiety and depression were present in 41 % of dissatisfied patients, and only in 10 % of satisfied patients after TKA. In a prospective study at 12 months after TKA, Bierke et al [26] found that patients with pre-operative psychopathologic factors, such as depression and somatization dysfunction, had a significantly greater pain at rest and during activities, lower knee function, and higher dissatisfaction. Similarly, other authors found that poor mental health score, depressive symptoms, and anxiety were predictive of long-term pain and knee functional impairment [23,27].…”
Section: Discussionmentioning
confidence: 97%
“…Ali et al [8] reported that anxiety and depression were present in 41 % of dissatisfied patients, and only in 10 % of satisfied patients after TKA. In a prospective study at 12 months after TKA, Bierke et al [26] found that patients with pre-operative psychopathologic factors, such as depression and somatization dysfunction, had a significantly greater pain at rest and during activities, lower knee function, and higher dissatisfaction. Similarly, other authors found that poor mental health score, depressive symptoms, and anxiety were predictive of long-term pain and knee functional impairment [23,27].…”
Section: Discussionmentioning
confidence: 97%
“…In the past 7 years, more attention has been paid to the negative effects of presurgical psychological distress on patient satisfaction after TKA [ 13 , 14 , 29 32 ], leading to the improved presurgical assessment of patients and improved patient selection for surgery. One study revealed preoperative anxiety and/or depression to be an important factor predicting patient satisfaction after TKA [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although patients' expectations are the main factor contributing to patient satisfaction after TKA [6,8,16,[25][26][27][28], the role of psychological factors has been paid more attention in recent years [13,14,24,26,[29][30][31][32][33][34][35]. One study found higher levels of 90-day readmission, dissatisfaction, and burden for healthcare providers among patients with depression [33].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoartrit hastalarında önce sadece ağrı olurken ilerleyen dönemlerde eklem tutukluğu olması ile günlük yaşam aktiviteleri de kısıtlanmaktadır 29 . Kronik ağrılı ve yaşam aktiviteleri belli alanlarda kısıtlanmış hastaların psikiyatrik eş hastalanma oranları oldukça yüksektir ve en sık depresif bozukluk görülmektedir [30][31][32] . Osteoartrit hastalarının cerrahi girişim öncesi sağlıklı kontrollerle karşılaştırıldığı bir çalışmada; OA hastalarının duygulanımlarının depresif olduğu ve öz kıyım düşüncelerinin fazla olduğu tespit edilmiştir 32 .…”
Section: İstatistiksel Analizunclassified